2014
DOI: 10.1063/1.4896846
|View full text |Cite
|
Sign up to set email alerts
|

Control of waveguide properties by tuning femtosecond laser induced compositional changes

Abstract: Articles you may be interested in Optical characterization of femtosecond laser induced active channel waveguides in lithium fluoride crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 25 publications
4
34
0
2
Order By: Relevance
“…Waveguide writing, optical and structural characterization details have already been described in detail in previous works . The waveguide inscription setup is based on a high repetition rate fs‐laser (Tangerine, Amplitude Systems, 500 kHz rep. rate) emitting ≈400 fs pulses at 1030 nm.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Waveguide writing, optical and structural characterization details have already been described in detail in previous works . The waveguide inscription setup is based on a high repetition rate fs‐laser (Tangerine, Amplitude Systems, 500 kHz rep. rate) emitting ≈400 fs pulses at 1030 nm.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that fs‐laser induced local modification of the glass composition has been shown to provide an extremely efficient alternative for the production of high performance passive waveguides, waveguide optical amplifiers and lasers . We have shown that in several glass families including phosphates, tellurites, and borates, it is feasible producing high contrast waveguides by inducing the migration of an index carrier element (La, Te, …) toward the guiding region by fs‐laser irradiation at high repetition rate. The migration of the carrier index element occurs along with the cross migration of a fast diffusing element, normally an alkaline (Na, K).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations